Vaccine Effectiveness Against Influenza-Associated Hospitalizations Among Adults, 2018–2019, US Hospitalized Adult Influenza Vaccine Effectiveness Network. (18th December 2020) - Ferdinands, Jill M; Gaglani, Manjusha; Ghamande, Shekhar; Martin, Emily T; Middleton, Donald; Monto, Arnold S; Silveira, Fernanda; Talbot, Helen K; Zimmerman, Richard; Smith, Emily R; Patel, Manish; ,
Abstract: We estimated vaccine effectiveness (VE) for prevention of influenza-associated hospitalizations among adults during the 2018–2019 influenza season. Adults admitted with acute respiratory illness to 14 hospitals of the US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN) and testing positive for influenza were cases; patients testing negative were controls. VE was estimated using logistic regression and inverse probability of treatment weighting. We analyzed data from 2863 patients with a mean age of 63 years. Adjusted VE against influenza A(H1N1)pdm09–associated hospitalization was 51% (95% confidence interval [CI], 25%–68%). Adjusted VE against influenza A(H3N2) virus–associated hospitalization was −2% (95% CI, −65% to 37%) and differed significantly by age, with VE of −130% (95% CI, −374% to −27%) among adults 18 to ≤56 years of age. Although vaccination halved the risk of influenza A(H1N1)pdm09–associated hospitalizations, it conferred no protection against influenza A(H3N2)–associated hospitalizations. We observed negative VE for young and middle-aged adults but cannot exclude residual confounding as a potential explanation. Abstract : Influenza vaccination halved the risk of influenza A(H1N1)pdm09–associated hospitalizations but conferred no protection against influenza A(H3N2)–associated hospitalizations among adults enrolled in the HAIVEN study during the 2018–2019 US influenza season.